Simple Solar Homesteading - Alexander, LaMar (SunPower Publishing, 2012)
Simple Solar Homesteading: Self Help This book is for anyone who is thinking about or already living off grid and wants to learn how to build simple solar homesteading projects to make life easier. Included in this book are complete plans for several projects and all plans include pictures, step by step directions, cost and material list.